O ACADÊMICO DE ENFERMAGEM NA REABILITAÇÃO PSICOSSOCIAL DE INDIVÍDUOS EM SOFRIMENTO PSÍQUICO - Frohlich, Mariana; Cruz, Cibele T. d.; Menin, Gisele E.; Oliveira, Rosilda d.; Piccoli, Jaqueline; Stumm, Eniva M. F. (Salão do Conhecimento, 2013)
Resumo